Review of Maritime Transport 2022 - United Nations Conference on Trade; Development (United Nations, 2022)
The Review of Maritime Transport (RMT) has been published annually since 1968. The flagship report provides an analysis of structural and cyclical changes affecting seaborne trade, ports and shipping, as well as an extensive collection of statistics. Around 80% of the volume of international trade in goods is carried by sea, and the percentage is even higher for most developing countries. The 2022 RMT covers recent developments in maritime logistics related to the Covid-19 pandemic, the war in Ukraine, and a special chapter on consolidation and competition issues in container shipping.